Impact of Total quality management on cleaning companies in Finland : A Focus on organisational performance and customer satisfaction - Kola Olayiwola, Rasheed; Tuomi, Ville; Strid, Jörgen; Nahan-Suomela, Rosmeriany (Elsevier, 2024)
The importance of TQM in cleaning companies in Finland is investigated in this study. The theoretical framework, TQM practices, and the relationship between TQM implementation and customer satisfaction among cleaning companies in Finland were all examined. It was discovered that employee and communication management increases service quality and boosts organisational performance. The study also discovered that in cleaning organisations, organsational performance has a favourable and significant relationship with customer satisfaction, as well as a positive correlation between employee, communication management, and customer satisfaction. Meanwhile, according to the results of a correlation analysis based on the Pearson correlation coefficient, the only factor limiting the implementation of Total Quality Management in Finnish cleaning organisations was resistance to change, as there were no preliminary signs of multicollinearity based on the two variables of the correlation coefficient criteria (r 0.70). Furthermore, the study adopted hierarchical multiple regression analysis to analyse the relationship between Total Quality Management and Organisational Performance. The results revealed that the two entities have a substantial association, providing valuable insights into the cleaner aspects of the study, particularly when considering organisational performance and customer satisfaction in the Finnish cleaning industry.
Keywords: Total Quality Management; Organisational Performance; Employee and communication management; Organisation’s performance; Finnish cleaning industry; Correlation analysis; Hierarchical multiple regression analysis; customer satisfaction; fi=Tuotantotalous|en=Industrial Management|